2023
DOI: 10.1073/pnas.2215376120
|View full text |Cite
|
Sign up to set email alerts
|

MYC-driven synthesis of Siglec ligands is a glycoimmune checkpoint

Abstract: The Siglecs (sialic acid-binding immunoglobulin-like lectins) are glycoimmune checkpoint receptors that suppress immune cell activation upon engagement of cognate sialoglycan ligands. The cellular drivers underlying Siglec ligand production on cancer cells are poorly understood. We find the MYC oncogene causally regulates Siglec ligand production to enable tumor immune evasion. A combination of glycomics and RNA-sequencing of mouse tumors revealed the MYC oncogen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 23 publications
(17 citation statements)
references
References 110 publications
(149 reference statements)
1
14
0
Order By: Relevance
“…In a fluorescence-based assay using chemically engineered glycans, sLewisA, sLewisX and sTn were identified as the most prominent glycans that bind Siglec-9. Binding of Siglec-9 to sLewisX has been previously described ( 67 ) and recently, sLewisA and sLewisX have been reported as MYC-driven ligands of Siglecs ( 68 ). The breast tumor cell lines used in our study express low levels of sLewisA/CA19-9 and high levels of sLewisX on the cell surface.…”
Section: Discussionmentioning
confidence: 78%
“…In a fluorescence-based assay using chemically engineered glycans, sLewisA, sLewisX and sTn were identified as the most prominent glycans that bind Siglec-9. Binding of Siglec-9 to sLewisX has been previously described ( 67 ) and recently, sLewisA and sLewisX have been reported as MYC-driven ligands of Siglecs ( 68 ). The breast tumor cell lines used in our study express low levels of sLewisA/CA19-9 and high levels of sLewisX on the cell surface.…”
Section: Discussionmentioning
confidence: 78%
“…Previous studies have shown that Siglec-7 and Siglec-9 ligands are found on O-glycans (62,(67)(68)(69). Siglec-7 and -9 and their murine equivalent Siglec-E have been shown previously to be important glyco-immune checkpoints, directly promoting a protumour macrophage phenotype which can suppress cytotoxic CD8 + T cells (15,21,58).…”
Section: Discussionmentioning
confidence: 99%
“…Siglec-E is considered a Siglec-7 and Siglec-9 ortholog/paralog in mice (61). Siglec-E has been broadly described as a key glyco-immune checkpoint in multiple cancers and targeting of Siglec-E has been shown to repolarise immunosuppressive macrophages towards proinflammatory phenotype (15,61,62). We profiled expression of Siglec-E throughout the TIME in our syngeneic allograft model.…”
Section: St3gal1-biosynthesised Siglec Ligands Are Critical Glyco-imm...mentioning
confidence: 99%
“…The same study noted that a single supplier offers 287 unique antibodies to tubulin and 269 unique antibodies to CD4, meaning that there are more antibodies to these two proteins available from a single supplier than all the commercially available anti-glycan antibodies combined. Further complicating monoclonal antibody development is the fact that many lectin receptors have multiple ligands that are expressed in the context of cancer 10,15,17,23,29 , and often the precise identities of their ligands are unknown. “Decoy receptor” molecules composed of a lectin glycan-binding domain fused to an antibody Fc domain address this complexity by retaining native glycan-binding specificities; however, their low binding affinities (typically with K D s in the μM to mM range 30 ) preclude their use as therapeutics.…”
Section: Mainmentioning
confidence: 99%